THE PLACE OF DOCUMENTATION RESEACH IN THE SYSTEM OF SCIENCES - ZINKEVIČIENĖ, JULIJA (Knygotyra, 2015)
The documents preserve the social experience of the humanity and, thus, provide concentrated knowledge to the society and individuals, help to transfer experience to the future generations. The goal of the article is to analyze the documentation (research) as an interdisciplinary branch of science and study area, its place and role within the system of communication and informatikon sciences. The main attention should be focused on the influence of the archival research and its interaction with other branches. The documentation research is a basic discipline that helps to transfer a complex of general theoretical knowledge in educating the bachelors of information and communication science. Without regard to a chosen direction of studies, each student has to acquire knowledge about a document and documentary communication. They have to be able to understand different concepts of a document that are used abroad and our country. The definition and place of documentation research is an important issue discussed by the scientists. During the last 10–15 years it turned into a general university discipline taught in many departments of humanities and social sciences abroad. The quick spread and development of documentation research has instigated discussions about its place within the system of sciences. As an autonomous branch of science documentation research has a place among other branches within the system of communication and information sciences. It investigates the stucture, atributes, and functions of a document. The document becomes a general concept in communication and informatikon sciences. That allows us to treat documentation research as an interdisciplinary branch of science.